Morbidity profile and short-term outcomes of low birth weight neonates delivered in a tertiary care centre: a prospective observational study - Nazira, K.; Ali, Syed Manazir; Firdaus, Uzma (International Journal of Contemporary Pediatrics, 2022)
Background: More than 20 million babies (15%) born worldwide are LBW (low birth weight) out of which 90% belong to developing countries. Identification of the timing and pattern of morbidities is expected to aid in the timely management of LBW neonates. Objective of the current study was to determine the morbidity profile and short-term outcomes (3 months) in LBW babies. Methods: Prospective observational study was conducted in neonatal section, JNMCH, AMU, Aligarh, UP over a period of 2 years which included LBW neonates (n=266) who were regularly screened for the occurrence as well as severity of defined morbidities. Immediate outcome was noted in the form of recovery or mortality and 3 months follow up was done for assessment of growth and development as well as occurrence of complications. Results: RDS was found as the major morbidity seen in 35% (n=93) followed by sepsis 27.8% (n=74), jaundice 24% (n=63), MAS 21.4% (n=57). On logistic regression analysis, MAS (OR=21) followed by sepsis (OR=9.1) and RDS (OR=4.6) were the common predictors for mortality. Follow-up of 221 babies demonstrated readmission in 9% babies (n=20) with high rate of admission among moderate preterm 45% (n=9) and top fed infants 85% (n=17), 2 succumbed to LOS, signs of developmental lag in 2.7% (n=6), ROP in 3% (n=7) and 7 showed neurological findings on ultrasonography. Conclusions: Present study has shown MAS, RDS and sepsis as predominant causes of neonatal morbidity and mortality which could be prevented through early identification and timely intervention. Proper counselling at discharge and regular follow-up is equally vital to improve their neurodevelopmental outcome.